Mapping the unrapeability of white and black womxn. Issue 4 (2nd October 2018) - Helman, Rebecca
Abstract: Redi Thlabi's book Khwezi: The Remarkable Story of Fezekile Ntsukela Kuzwayo, published in September 2017, recalled national attention to the 2006 Jacob Zuma rape trial, a deep scar on the body of our democracy. Thlabi's book demonstrates the cost incurred by a womxn who accused a powerful man of rape. During the trail Zuma's lawyer, Advocate Kemp, repeatedly implied that Kuzwayo was sexually promiscuous and therefore 'unrapeable'. This idea – that the rapes of certain womxn do not count as harm – shapes the way in which South African society responds (or fails to respond) to contemporary instances of sexual violence in significant ways. This article aims to interrogate the notion of 'un/rapeability' and, in particular, to situate it in relation to the colonisation of land, as well as the intersecting racialised and gendered formations of coloniality. A central process of colonising the land of South Africa was the establishment of racialised and gendered dynamics of control: the conquering of both 'black' and 'white' womxn. While white womxn were possessed as reproducers of race, black womxn were possessed as not-womxn. These racialised, gendered constructions have produced complexly disparate notions of respectability and harm, in relation to which only certain womxn, at particular historical moments and under certain circumstances, are able to claim status as 'legitimate' victims/survivors of rape. In elucidating the uneven nature of the contemporary landscape of sexual violence, this article aims to trouble the notion that some womxn are 'unrapeable' and therefore unharmed by the sexual violations enacted upon them.